The Pollen Sequence of Les Échets (France): A New Element for the Chronology of the Upper Pleistocene - de Beaulieu, Jacques-Louis; Reille, Maurice (Géographie physique et Quaternaire, 1984)
ABSTRACTLes Échets mire (near Lyon, France) is one of the very few European sites showing an almost continuous record from the glaciation that preceded the Eemian up to now. The pollen diagram can easily be correlated with those from Grande Pile (Vosges). On the basis of a comparison between the two sequences, the age of three clearly temperate post-Eemian episodes (Saint-Germain Ia, Ic and Il at Grande Pile) is discussed. The authors correlate these episodes with the Early Würm Interstadials of Amersfoort, Brorup and Odderade described in Northern Europe and accept the chronology of Grande Pile that dates Saint-Germain I and Saint-Germain Il between ca 115 000 and 70 000 BP, thus making them equivalents of deep sea isotopic stages 5c and 5a. This leads to refute the 14C chronology admitted up to now that places the Early Würm between 75 000 and 55 000 BP. Considering the predominant temperate episodes during this period, the authors propose to use the term "Pre-Würm" instead of "Early Würm". During the Middle Würm, three not well-marked interstadials can be recognized. No interstadial is found during the late Pleni-Würm.